Understanding world Christianity : eastern Africa - Kollman, Paul V.; Smedley, Cynthia Toms, 1975- (Understanding world Christianity series., 2018)
In this exciting volume, Paul Kollman and Cynthia Toms Smedley offer an introduction to Eastern African Christianity that has been desperately needed by scholars, students, and interested readers alike. Short, engaging chapters help readers understand the complexity of Christianity in the region and broaden their understanding of the region itself. Readers will understand the interplay of Christianity and culture, and will see how geography, borders, economics, and other factors influence Christian faith.